Implementasi Penilaian Non-Tes Mahārah Kalām: Studi Kasus Multisitus di Perguruan Tinggi Yogyakarta - Cahya Edi Setyawan; Zulaeha; Akhsan; Nada Ibrahim Alribdi; Ahmadi M (Alsina : Journal of Arabic Studies, 2025)
Non-test assessment is an evaluation method that focuses on students’ processes and performance in real contexts without relying on written examinations. This study aims to analyze the implementation of non-test assessment in the mahārah kalām (speaking skills) course at three higher education institutions: STAI Masjid Syuhada (STAIMS), Universitas Muhammadiyah Yogyakarta (UMY), and UIN Sunan Kalijaga Yogyakarta (UIN Suka). Employing a multi-site case study with a descriptive qualitative approach, data were collected through in-depth interviews, participatory classroom observations, and analysis of assessment documents and student outputs. The findings reveal diverse strategies tailored to each institution’s characteristics. STAIMS applies a project-based assessment by producing Arabic-language vlogs to enhance communication, creativity, and digital literacy. UMY adopts a process-based approach through simulations and role-play, enabling gradual skill development with direct feedback. UIN Suka relies on intensive muḥādathah and khiṭābah minbarīyah practices to refine fluency and formal rhetoric. All three models are grounded in authentic and performance-based assessment principles, evaluating competence contextually, applicatively, and holistically. This study underscores that diverse approaches can complement one another in developing Arabic speaking proficiency, offering comparative insights into locally adapted pedagogical innovations aligned with learners’ needs and learning contexts.